Effect of fatigue life to the natural frequency of metallic component - Muhamad Aizuddin , Abdul Aziz (2013)
The effect of natural frequency to the fatigue life of the metallic material was studied over the entire fatigue life process. This study involves the fatigue tests that were carried out on rotating bending machine; at the same time, by means of modal testing, natural frequencies at different life stages were measured. The results of the experimental study showed that the changes of the specimens’ natural frequencies varied non-linearly with the number of cycle. It is also noticed that the relatively large changes in the natural frequency happened near the end of the fatigue life